A comment on Giusti et al. (2020) "Mussels (Mytilus spp.) products authentication: A case study on the Italian market confirms issues in species identification and arises concern on commercial names attribution, Food Control Volume 118, December 2020, 107, 379". (March 2021) - Araneda, Cristian; Pardo, Miguel Ángel; Jiménez, Elisa; Longa, Ángeles; Lee, Ren-Shiang; Segura, Cristian; Zbawicka, Malgorzata; Wenne, Roman; Gardner, Jonathan P.; Larraín, María Angélica
Highlights: Species identification in Mytilus spp. with taxonomically non-curated data base is error prone. Muti-locus analysis is the best approach for a trustworthy species identification in Mytilus spp. For seafood trade M. chilensis and M. galloprovincialis should be labeled as separated species.